Comparison of clinical and oncologic effectiveness between flexible 3-dimensional and bidimensional video-thoracoscopic surgery for lung cancer. Issue 3 (June 2021) - Pardolesi, Alessandro; Rolli, Luigi; Scanagatta, Paolo; Duranti, Leonardo; Tavecchio, Luca; Pastorino, Ugo
Background: Three-dimensional (3D) vision systems are available for video-assisted thoracic surgery (VATS). It is unclear whether 3D-VATS is superior to bidimensional (2D) VATS systems. Methods: We analyzed patients who received 3D-VATS ( n = 171) or 2D-VATS ( n = 228) lobectomy in a single institutional retrospective comparative study of 399 patients with resectable lung cancer conducted from June 2012 to December 2017. The operative and perioperative data were compared between the 2 groups. Results: Operative time, length of hospital stay, number of dissected lymph nodes, and rate of postoperative complications were similar in both groups. In the 3D group, there was no conversion to thoracotomy for intraoperative major vascular injuries, while conversion to an open procedure for uncontrolled bleeding was recorded in 4 (1.7%) patients in the 2D group. Reoperation for hemostasis and/or aerostasis occurred in 6 (2.6%) patients of the 2D group ( p = 0.04). Conclusion: Nonrandomized comparison of different surgical approaches is challenging. In our experience, 3D-VATS was safe and effective and offered excellent operative perception and sensitivity, enabling safer dissection of hilar structures. The 3D-VATS system helped skilled surgeons beyond the boundaries of more oncologically aggressive surgery.